Communication, Flexibility, and Resilience: Navigating the Shift to Virtual Service-Learning During COVID-19. (December 2021) - Reif-Stice, Carrie; Smith-Frigerio, Sarah
Major disruptions to traditional academic learning have occurred since the onset of the COVID-19 pandemic, as most higher education institutions have shifted to online or hybrid course delivery. This virtual shift has significant implications for service-learning. In this study, we explored the impact of virtual service-learning on public relations instructors and community partners. Interview respondents described challenges to virtual service-learning related to the pandemic but also noted unanticipated benefits, such as creativity and resilience. In addition, community partners and public relations instructors recommended a heightened focus on communication, flexibility, and adaptability to ensure successful virtual service-learning experiences for students and organizations.